2020
DOI: 10.3390/ijms21186704
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Casting Concentration on the Mechanical and Optical Properties of FA/CaCl2-Derived Silk Fibroin Membranes

Abstract: In this study, we describe the manufacturing and characterization of silk fibroin membranes derived from the silkworm Bombyx mori. To date, the dissolution process used in this study has only been researched to a limited extent, although it entails various potential advantages, such as reduced expenses and the absence of toxic chemicals in comparison to other conventional techniques. Therefore, the aim of this study was to determine the influence of different fibroin concentrations on the process output and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
(82 reference statements)
1
3
0
Order By: Relevance
“…No cytotoxic effects could be observed, neither in the functionalized membranes with EVs nor in the control group. Similar results could already be presented in previous studies from our research group 33 , 51 . The enhanced viability observed for L929 cells in both SF with EVs and SF without EVs compared to the toxic control group suggests a potential protective effect against the tested toxic agent.…”
Section: Discussionsupporting
confidence: 92%
“…No cytotoxic effects could be observed, neither in the functionalized membranes with EVs nor in the control group. Similar results could already be presented in previous studies from our research group 33 , 51 . The enhanced viability observed for L929 cells in both SF with EVs and SF without EVs compared to the toxic control group suggests a potential protective effect against the tested toxic agent.…”
Section: Discussionsupporting
confidence: 92%
“…We quantitatively analyzed their beneficial impact on keratinocyte activity and the overall dynamics of wound healing. Our previous studies have already revealed that additive-free electrospun nonwovens [ 28 ] and formic acid/CaCl 2 -derived silk fibroin membranes [ 29 ] exhibit high biocompatibility and regenerative properties supporting fibroblast adhesion and proliferation. In here, biocompatibility was affirmed through both direct and indirect assays, indicating viability levels that closely mirrored or surpassed control conditions, with the membranes and nonwovens showing low cytotoxic levels well below the 30% threshold.…”
Section: Discussionmentioning
confidence: 99%
“…Silk fibroin aqueous solution was obtained using PureSilk ® technology (Fibrothelium GmbH, Aachen, Germany), enabling medical grade quality production of silk on an industrial scale for a broad range of concentrations. Briefly, fibroin was separated from sericin by degumming it in hot alkali solution before dissolving it in a proprietary non-toxic solvent system based on Ajisawa’s reagent [ 28 , 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation